2019
DOI: 10.7554/elife.51423
|View full text |Cite
|
Sign up to set email alerts
|

Agonist-specific voltage-dependent gating of lysosomal two-pore Na+ channels

Abstract: Mammalian two-pore-channels (TPC1, 2; TPCN1, TPCN2) are ubiquitously- expressed, PI(3,5)P2-activated, Na+-selective channels in the endosomes and lysosomes that regulate luminal pH homeostasis, membrane trafficking, and Ebola viral infection. Whereas the channel activity of TPC1 is strongly dependent on membrane voltage, TPC2 lacks such voltage dependence despite the presence of the presumed ‘S4 voltage-sensing’ domains. By performing high-throughput screening followed by lysosomal electrophysiology, here we i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
50
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(55 citation statements)
references
References 50 publications
5
50
0
Order By: Relevance
“…Amitriptyline clomipramine, desipramine, imipramine, and nortriptyline were the five LyNa-VA1.x, and were categorised as tricyclic antidepressants (TCAs). Chlorpromazine and triflupromazine were the two LyNa-VA2.x identified, and were also recognised as tricyclic antipsychotics [ 71 ]. All seven identified molecules could act as agonist voltage-dependent gating modulators for both TPC1 and TPC2 [ 71 ].…”
Section: Pharmacological Modulators Of Tpcsmentioning
confidence: 99%
See 2 more Smart Citations
“…Amitriptyline clomipramine, desipramine, imipramine, and nortriptyline were the five LyNa-VA1.x, and were categorised as tricyclic antidepressants (TCAs). Chlorpromazine and triflupromazine were the two LyNa-VA2.x identified, and were also recognised as tricyclic antipsychotics [ 71 ]. All seven identified molecules could act as agonist voltage-dependent gating modulators for both TPC1 and TPC2 [ 71 ].…”
Section: Pharmacological Modulators Of Tpcsmentioning
confidence: 99%
“…Chlorpromazine and triflupromazine were the two LyNa-VA2.x identified, and were also recognised as tricyclic antipsychotics [ 71 ]. All seven identified molecules could act as agonist voltage-dependent gating modulators for both TPC1 and TPC2 [ 71 ]. Conversely, the study observed no significant activation of TPCs with carbamazepine (an anticonvulsant) and phenothiazine (an antipsychotic), which share a similar chemical structure with TCAs (the tricyclic ring).…”
Section: Pharmacological Modulators Of Tpcsmentioning
confidence: 99%
See 1 more Smart Citation
“…None of these compounds was found to activate TRPML1. Clomipramine (38) and desipramine (39) also activate TPC1 in a voltage-dependent manner, while chlorpromazine (43) inhibits TPC1 [14]. Hence, additional analysis of structure-activity relationships is needed, as slight changes in structures seemingly can reverse the activity on two-pore channel isoforms.…”
Section: Discussionmentioning
confidence: 99%
“…It has also been postulated that mammalian TPCs are not Ca 2+ release channels activated by NAADP, but rather Na + release channels activated by PI(3,5)P 2 [23,31]. The discovery of novel lipophilic small molecule agonists for TPCs in two independent high-throughput calcium imaging campaigns [127,128] partially reconciled this debate. Both campaigns revealed that TPC agonists can be identified in calcium imaging experiments, suggesting that TPCs are indeed permeable to Ca 2+ .…”
Section: Tpcs In Metazoamentioning
confidence: 99%